Diets of men and women in rural Bangladesh are equitable but suboptimal - Coleman, Fiona M.; Ahmed, Akhter; Quisumbing, Agnes R.; Roy, Shalini; Hoddinott, John F. (Elsevier, 2023)
Background: Recent evidence suggests that diet inequities between men and women may have diminished within rural Bangladeshi households. However, this has not been directly tested with appropriate physiologic adjustments and it is unclear whether changes have occurred across socioeconomic strata. Understanding intrahousehold dietary patterns at different points on the income and food-security distribution in rural Bangladesh—particularly, within ultrapoor and farm households—is important for appropriate design of gender-sensitive and nutrition-sensitive interventions, which often target these groups. Objective: Using 2012 and 2016 data, we aimed to examine gender differences in diet quantity and quality among ultrapoor and farm households in rural Bangladesh. Methods: The study used baseline 24-h dietary data from 2 randomized control trials conducted in rural Bangladesh: the Transfer Modality Research Initiative (ultrapoor households) and the Agriculture, Nutrition, and Gender Linkages project (farm households). Ordinary least squares regressions with household-level fixed effects tested for gender differences among constructed diet measures, such as caloric intake, caloric adequacy ratio, dietary diversity score, global diet quality score, and probability of consuming moderate or high levels of healthy food groups. Results: In both samples, on average, women consumed fewer calories than men in the same households but consumed near equal or more in reference to their caloric needs. Women scored <1% lower than men on diet quality indicators and showed similar probabilities to men of consuming healthy foods. Most men and women in both samples were calorically inadequate (>60%) and recorded poor diet quality scores that indicated high risk of nutrient inadequacy and chronic disease (>95%). Conclusions: In both ultrapoor and farm households, although men record higher intake quantities and diet quality scores, the apparent male advantage disappear when energy requirements and the magnitudes of difference are considered. Diets of men and women in these rural Bangladeshi households are equitable but suboptimal.